The CpG island methylator phenotype in breast cancer is associated with the lobular subtype - Rößler, Jessica; Ammerpohl, Ole; Gutwein, Jana; Steinemann, Doris; Schlegelberger, Brigitte; Weyer, Veronika; Sariyar, Murat; Geffers, Robert; Arnold, Norbert; Schmutzler, Rita; Bartram, Claus R.; Heinrich, Tilman; et al. (Epigenomics, 2015)
Background: Aberrations in DNA methylation patterns are well-described in human malignancies. However, the existence of the ‘CpG island methylator phenotype’ (CIMP) in human breast cancer is still controversial. Materials & methods: Illumina's HumanMethylation 450K BeadChip was used to analyze genome-wide DNA methylation patterns. Chromosomal abnormalities were determined by array-based CGH. Results: Invasive lobular breast carcinomas exhibit the highest number of differentially methylated CpG sites and a strong inverse correlation of aberrant DNA hypermethylation and copy number alterations. Nine differentially methylated regions within seven genes discriminating the investigated subgroups were identified and validated in an independent validation cohort and correlated to a better relapse-free survival. Conclusion: These results depict a clear difference between genetically and epigenetically unstable breast carcinomas indicating different ways of tumor progression and/or initiation, which strongly supports the association of CIMP with the lobular subtype and provide new options for detection and therapy.